Concert cycle of the Vienna Philharmonic, Salzburg, July 13-27, 1940 - Wiener Philharmoniker::::::::::::::: (Steyrermühl; Vienna; Austria, 2020)
Program for the cycle of concerts by the Vienna Philharmonic between July 13-27, 1940, conducted by Hans Knappertsbusch. The first program included Beethoven's Leonore Overture no. 3 and the fourth program included his Symphony no. 7, op. 92. A "serenade" concert by the wind musicians included the Rondino in E-flat, WoO 25.